Suku Aneuk Jamee: Diaspora Masyarakat Minang di Tanah Aceh (Kajian Historis dan Kehidupan Sosial Budaya) - Septian Fatianda (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2022)
This article discusses the diaspora carried out by the Minang people in West Sumatra to the land of Aceh from the perspective of history and socio-cultural life. In its development, the Minang community has acculturated with local culture in Aceh so as to form a new identity known as the aneuk jamee tribe. To answer this research problem, the historical method is used which consists of four steps, namely heuristics, verification, interpretation, and historiography. The process of diaspora Minang society has occurred since the 17th century when the Kingdom of Aceh made cultural contact because it became the ruler in the western part of Sumatra. Furthermore, after the outbreak of the Padri war, this diaspora wave increased because many Minang people as victims of this war chose to migrate in search of a better life. In Aceh, the Aneuk Jamee tribal people are scattered by inhabiting residential areas on the west coast of Aceh.